Evaluation of surgical procedures in primary mediastinal cysts and tumors: single-center experience - Kermenli, Tayfun (Kardiochir Torakochirurgia Pol, 2019)
AIM: In this study, we aimed to evaluate the results of our patients with a primary mediastinal mass and the surgical techniques applied in our clinic retrospectively. MATERIAL AND METHODS: Between March 2015 and March 2019, the results and treatment protocols of 32 patients with a primary mediastinal mass or cysts who were followed up and treated in our clinic were evaluated retrospectively. Twenty-six patients who underwent surgery for biopsy or resection were included in the study. RESULTS: Sixteen of our patients were male and 10 were female. The mean age was 39 years. 80.2% of our patients were symptomatic and 19.2% were asymptomatic and a mediastinal mass was incidentally detected in these asymptomatic patients. The most common symptom was dyspnea with frequency of 38.4%. In terms of localization, the mass was lateralized on the right side in 7 patients, on the left side in 5 patients. In 13 patients, the tumor was located in the posterior mediastinum. 8 patients underwent anterior mediastinotomy and 1 patient underwent biopsy with video-assisted thoracoscopic surgery (VATS). Most commonly a thymus-derived mass was seen. Fifteen patients underwent excision with VATS, 3 thoracotomy, 2 sternotomy and in 1 patient VATS assisted anterior minithoracotomy was performed. CONCLUSIONS: Mediastinal tumors and cysts have different histopathological features. Robotic surgery and VATS-assisted surgery are increasingly used in surgical excision.